FUNCTIONAL FOODS OR PHYTOCHEMICALS, CLASSIFICATION AND IMPORTANCE - Chasquibol S., Nancy (2003)
We described the benefits of funtional or phytochemicals foods in disease prevention and health promotion. This article is a contribution for the development of this new research area.